Stoichiometric models of sucrose and glucose fermentation by oral streptococci: Implications for free acid formation and enamel demineralization. Issue 4 (April 2023) - Mansouri, Marzieh; O'Brien, Evan P.; Mondal, Karabi; Chen, Chien-Chia; Drummond, James L.; Hanley, Luke; Rockne, Karl J.
Abstract: Objectives: The objective of this study is to develop stoichiometric models of sugar fermentation and cell biosynthesis for model cariogenic Streptococcus mutans and non-cariogenic Streptococcus sanguinis to better understand and predict metabolic product formation. Methods: Streptococcus mutans (strain UA159) and Streptococcus sanguinis (strain DSS-10) were grown separately in bioreactors fed brain heart infusion broth supplemented with either sucrose or glucose at 37 °C. Cell mass concentration and fermentation products were measured at different hydraulic residence times (HRT) to determine cell growth yield. Results: Sucrose growth yields were 0.080 ± 0.0078 g cell/g and 0.18 ± 0.031 g cell/g for S. sanguinis and S. mutans, respectively. For glucose, this reversed, with S. sanguinis having a yield of 0.10 ± 0.0080 g cell/g and S. mutans 0.053 ± 0.0064 g cell/g. Stoichiometric equations to predict free acid concentrations were developed for each test case. Results demonstrate that S. sanguinis produces more free acid at a given pH than S. mutans due to lesser cell yield and production of more acetic acid. Greater amounts of free acid were produced at the shortest HRT of 2.5 hr compared to longer HRTs for both microorganisms and substrates. Significance: The finding that the non-cariogenic S. sanguinis produces greater amounts of free acids than S. mutans strongly suggests that bacterial physiology and environmental factors affecting substrate/metabolite mass transfer play a much greater role in tooth or enamel/dentin demineralization than acidogenesis. These findings enhance the understanding of fermentation production by oral streptococci and provide useful data for comparing studies under different environmental conditions.